2018
DOI: 10.1371/journal.pone.0193786
|View full text |Cite
|
Sign up to set email alerts
|

Ptolemaic military operations were a dominant factor in the spread of Egyptian cults across the early Hellenistic Aegean Sea

Abstract: Early in the Ptolemaic era, Egyptian cults, particularly those of Isis and Sarapis, spread successfully to ports across the ancient Aegean Sea. Leading researchers in the field claim that the spread of these cults was influenced by multiple factors, ones that were mainly economic or political in character. However, the question of which factors had more weight or impact than others in the process of the early spread of Egyptian cults has not yet been answered in academic discussion. This could be related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The results of our previously published research, which focused on quantitative evaluation of the impact of individual factors on the spread of the Isiac cults across the ancient Aegean Sea [15], demonstrated that Bricault's view is a promising premise. Informed by multivariate statistical analysis, we reached in our previous article the conclusion that the early spread of the Isiac cults across the islands in the Aegean Sea was promoted by military and commercial activities of the Ptolemaic dynasty, although the model presented there identified the Ptolemaic military operations as the most influential factor in the process of the spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our previously published research, which focused on quantitative evaluation of the impact of individual factors on the spread of the Isiac cults across the ancient Aegean Sea [15], demonstrated that Bricault's view is a promising premise. Informed by multivariate statistical analysis, we reached in our previous article the conclusion that the early spread of the Isiac cults across the islands in the Aegean Sea was promoted by military and commercial activities of the Ptolemaic dynasty, although the model presented there identified the Ptolemaic military operations as the most influential factor in the process of the spread.…”
Section: Introductionmentioning
confidence: 99%
“…The geocoding of historical and archaeological data has further invited the application of spatial network analysis [21][22][23][24] and agent-based modeling [25]. Both the research presented here and our previous work concerning the diffusion of the Isiac cults across the ancient Aegean Sea draw on these developments [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the method of spatial proximity analysis was applied to quantitatively test the established hypothesis that soldiers were one of the major factors in the dissemination of ancient cults [7][8][9][10][11]. This hypothesis has recently been examined in connection to the cult of Asclepius in the Roman period by Ghislaine van der Ploeg.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the combination of established methods and formal approaches (e.g., network analysis, GIS, agent-based modeling, quantitative textual analysis) has demonstrated significant potential for the historiography of the ancient Mediterranean (and beyond) [8,[10][11][12][13][14][15][16][17][18][19][20][21]. The present article follows this academic trend and reveals, by means of a GIS proximity analysis based on the platform of Roman transportation road network, specific spatial patterns in the worship of Asclepius in the military environment in the provinces along a portion of the border of the Roman Empire leading from Britannia to Moesia Inferior (i.e., Britannia, Germania Superior and Inferior, Raetia, Noricum, Pannonia Superior and Inferior, Dacia, and Moesia Superior and Inferior, Fig 1).…”
Section: Introductionmentioning
confidence: 99%
“…Stark further evaluates the role of various cultural factors in the same process, like in hypothesis 3-3 (“Hellenic cities had Christian congregations sooner than did Roman cities”) and hypothesis 5-8 (“Cities with a significant Diasporan community were Christianized sooner than other cities”). Although we fully realize that cultural factors of this kind could be decisive for the spread of some other religious traditions in the ancient Mediterranean [8], we leave them out of our analysis as unnecessary for the explanation of the process of our interest.…”
Section: Introductionmentioning
confidence: 99%